Psychometric properties of the disciplinary attitudes questionnaire in psychology students - Patrón Espinosa, Felipe de Jesús; Ortega González, Mauricio; Viloria Hernández, Esperanza (IE Revista de Investigación Educativa de la REDIECH, 2023)
The purpose of this study was to explore the psychometric properties of the Questionnaire of disciplinary attitudes in Psychology students, as well as to identify if there's a correlation between the score obtained in said test and the semester of the course in which the psychology students are. A first version of the test was developed and applied to 351 psychology students in virtual mode. Subsequently, McDonald's Omega coefficient was used to determine the reliability of the instrument and an exploratory factor analysis was performed. Finally, the Spearman coefficient was used to determine the correlation between the test score and the semester of the course in which the psychology students are. From the exploratory factor analysis, 10 items had to be eliminated and a four-factor solution was revealed that didn't explain more than 50% of the variance. The correlation between the score of the test and the semester was weak and positive, which means that advancing in the career doesn't have much influence on the image that students share of psychology. Due to the findings, it is necessary to continue with more research that uses larger samples and from different regions and schools of the country.